БЎЛАЖАК ПЕДАГОГ - ПСИХОЛОГЛАРНИНГ АКМЕОЛОГИК КОМПЕТЕНТЛИГИНИНГ ИЖТИМОИЙ ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Даукеева, А. (SCIENCE and SOCIETY, 2023)
The theoretical and practical preparation of the acmeological competence of future pedagogical psychologists is defined as the unity of and the ability to pedagogical carry out professional activities.